Fields and possibilities of ecological development of tourism - Dávid, Lóránt (JOURNAL OF LANDSCAPE ECOLOGY, 2010)
Many efforts have already been made and several ideas have been promoted to solve the problems in the development of socially and economically underprivileged, peripheral areas. Most of the proposals suggest supporting rural tourism and its management based on local natural, cultural, agrarian etc. traditions and help them this way to catch up with the more developed regions of the country. According to our surveys it can be stated that sustainable and responsible rural tourism development is unbelievable without the application of ecological thinking. Consequently tourism ecology, as theory and practice, naturally helps developing the tourism of rural areas based on local natural, social and cultural resources. Sustenance of tourism is a double task: we have to provide long-term reservation and guarantee that entrepreneurs’ input of capital will return and their firm’s will better their economic etc state in the same time. Sustainable tourism has to be endurable and economically executable on the long term, but at the same time it has to be socially and ethically fair in relations to local people. Nevertheless, it is also a expectation that actors of the system, i.e. tourists must continue an active and responsibly sustainable practice (responsible sustainable tourism).